2020
DOI: 10.4103/joco.joco_91_20
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Outcomes of Limbal Allograft Transplantation in Eyes Having Limbal Stem Cell Deficiency

Abstract: Purpose: To report the limbal allograft transplantation and penetrating keratoplasty (PK) results in limbal stem cell deficiency (LSCD)-developed eyes because of chemical or thermal injury. Methods: Medical records of 18 eyes of 14 patients who had undergone keratolimbal allograft (KLAL) or living-related conjunctival limbal allograft (lr-CLAL) with or without PK and followed up at least 1 year postoperatively were evaluated retrospectively. The preoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…shows results of important CLAU studies. [35][36][37][38][39][40][41] In all studies surgical outcome was significantly better in autologous conjunctival limbal grafts as compared to live-related allogeneic grafts.…”
Section: Conjunctival Limbal Epithelial Transplantsmentioning
confidence: 81%
See 1 more Smart Citation
“…shows results of important CLAU studies. [35][36][37][38][39][40][41] In all studies surgical outcome was significantly better in autologous conjunctival limbal grafts as compared to live-related allogeneic grafts.…”
Section: Conjunctival Limbal Epithelial Transplantsmentioning
confidence: 81%
“…The survival rate in the 1 st , 2 nd and 3 rd year were 65%, 54% and 37% respectively. 41 Titiyal et al prospectively compared CLAL versus KLAL in unilateral chemical/thermal burn cases (20 cases) and found that the former was much better in terms of visual gain (80% v/s 50%) and ocular surface stability (70% v/s 20%) at 6 months. The mean age of the patients was around 17.5 years.…”
Section: Conjunctival Limbal Epithelial Transplantsmentioning
confidence: 99%
“…If autologous transplantation is not possible, keratolimbal allograft (KLAL) can be performed, in which the tissue is harvested from a cadaveric donor, which requires a living related donor or systemic immunosuppression with cyclosporin A prior to transplant to in order prevent graft rejection. Corneal graft clarity and visual improvement after KLAL have been reported during follow-up; however, incidents of rejection or LSCD recurrence have also been noted (Ozer et al 2020).…”
Section: Regenerative Therapies For Corneal Restorationmentioning
confidence: 99%
“…Transplantation: (1) Conjunctival limbal autograft (CLAU)[ 124 , 125 ]; (2) conjunctival limbal allograft (CLAL)[ 86 , 126 ]; (3) keratolimbal allograft (KLAL)[ 127 , 128 ]; (4) ex vivo cultivated limbal epithelial stem cells (CLET); (5) simple limbal epithelial transplantation (SLET); and (6) alternative cell population transplantation. In CLAU, CLAL and KLAL, since the long time for limbus transplantation from the donor to the stem cell deficient eye, healthy donor eyes have an increased risk of LSCD.…”
Section: Corneal Epithelial Stem Cellsmentioning
confidence: 99%